Kevlar nanofiber composite membrane and preparation method thereof

By crosslinking PVA-co-PE nanofibers with Kevlan nanofibers to form a dense layered mesh structure, the problem of insolid bonding of the existing composite membrane is solved, and the Kevlan nanofiber composite membrane is significantly improved Mechanical strength and durability are suitable for applications in composite and packaging materials.

CN119264482APending Publication Date: 2025-01-07WUHAN TEXTILE UNIV

Patent Information

Application Number
CN202411279324.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

During the use of the existing Kevlan nanofiber composite membrane, there are problems such as unsolid interface bonding and easy to delaminate or peel, and the uneven distribution of nanotubes leads to insufficient mechanical properties and durability.

Method used

By crosslinking a specific amount of PVA-co-PE nanofibers with Kevlan nanofibers, a Kevlan nanofiber composite film with dense stacked layered chimeric structure was prepared, and the crossing was carried out using concentrated hydrochloric acid, glutaraldehyde, etc. The coupling agent promotes hydrogen bond formation and cross-linking network between fibers, enhancing interface binding force.

Benefits of technology

It significantly improves the mechanical strength and durability of the composite membrane, ensures effective stress transmission, and the preparation method is simple and economical to operate, and has high reproducibility, suitable for expansion from laboratory to industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264482A_ABST
    Figure CN119264482A_ABST
Patent Text Reader

Abstract

The invention provides a Kevlar nanofiber composite membrane and a preparation method thereof, and relates to the field of nanofiber composite membrane preparation. The method comprises the following steps: respectively preparing a Kevlar nanofiber dispersion liquid and PVA-co-PE nanofibers, diluting the Kevlar nanofiber dispersion liquid to obtain a Kevlar nanofiber hydrogel, mixing the Kevlar nanofiber hydrogel with the PVA-co-PE nanofibers, adding a mixed solution of water and isopropanol and a cross-linking agent, and carrying out stirring, cross-linking, suction filtration and hot pressing to obtain the Kevlar nanofiber composite membrane. The cross section of the composite film is of a compactly stacked layered embedded structure, so that the composite film has excellent mechanical strength and durability, can effectively resist external stress, and avoids mechanical damage. In addition, due to the layered structure, the composite film has good machinability, processing operations such as cutting, coating and stacking can be conveniently carried out in practical application, and various industrial and engineering application requirements can be met. The preparation method provided by the invention is simple and convenient to operate, economical and efficient, has high reproducibility and is easy to realize industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiber composite membrane preparation, and in particular to a Kevlar nanofiber composite membrane and a preparation method thereof. Background Art

[0002] Kevlar fiber is a high-performance aramid fiber developed by DuPont. It has excellent mechanical properties, high heat resistance and chemical stability, and is widely used in aerospace, bulletproof materials, automotive industry and composite materials. However, the diameter of traditional Kevlar fiber is relatively large, usually between 10-12μm, which limits its application in certain fields that require high precision and high performance. With the development of nanotechnology, Kevlar nanofiber has gradually attracted widespread attention as a new type of material, and compounding Kevlar nanofiber with other materials to prepare Kevlar nanocomposite membrane with better performance has also become one of the research hotspots.

[0003] In the prior art, the patent with publication number CN110004712B discloses a method for preparing a high-strength thermal conductive film based on Kevlar nanofibers. The invention uses boron nitride nanosheets and Kevlar nanofibers as membrane material assemblies, and obtains Kevlar nanofiber thermal conductive films by vacuum filtration, crosslinking, etc. The disadvantage of this invention is that boron nitride nanosheets are an inorganic material with relatively inert chemical properties, resulting in a lack of effective chemical bonding or strong physical interaction between Kevlar nanofibers and boron nitride nanosheets, resulting in the interface bonding being not strong enough, and the two cannot be completely crosslinked by the immersion crosslinking method. These deficiencies may cause the composite film to delaminate or peel off during use.

[0004] In the prior art, the patent with publication number CN116407960A discloses a titanium dioxide flexible composite film based on Kevlar fiber and a preparation method thereof. The invention obtains a titanium dioxide flexible composite film by adding TiO2 nanotubes to a Kevlar nanofiber dispersion for blending, stirring, filtering and drying. The disadvantage of the invention is that the addition of titanium dioxide nanotubes by blending easily leads to the aggregation and uneven distribution of nanotubes. Compared with cross-linking through chemical bonds, blending makes the interface between Kevlar nanofibers and titanium dioxide nanotubes not firmly bonded, and is easy to fall off or slip under stress.

[0005] The problems existing in the above-mentioned prior art will affect the mechanical properties and durability of the composite membrane. In view of this, it is necessary to design an improved Kevlar nanofiber composite membrane material to solve the above-mentioned problems. Summary of the invention

[0006] The object of the present invention is to provide a Kevlar nanofiber composite membrane and a preparation method thereof, wherein a specific amount of PVA-co-PE (polyvinyl alcohol and polyethylene copolymer) nanofibers are cross-linked with Kevlar nanofibers to obtain a Kevlar nanofiber composite membrane having a densely stacked layered mosaic structure. The composite membrane provided by the present invention has excellent comprehensive performance, and its mechanical strength and durability are greatly improved compared with ordinary Kevlar nanofiber membranes, and has good application prospects in the fields of composite materials, packaging materials, and filter materials. The preparation method provided by the present invention is simple to operate, economical and efficient, has high reproducibility, and is easy to expand from laboratory scale to industrial production.

[0007] To achieve the above-mentioned object of the invention, the present invention provides a method for preparing a Kevlar nanofiber composite membrane, comprising the following steps:

[0008] S1, cutting the Kevlar fiber into small pieces, putting it into a potassium hydroxide aqueous solution, immersing it for 15-25 seconds, pouring a certain amount of dimethyl sulfoxide, and mechanically stirring it for 2-3 hours to obtain a Kevlar nanofiber dispersion with a mass volume fraction of 0.1%-0.5%; wherein the potassium hydroxide aqueous solution is prepared with ultrapure water, the volume ratio of the ultrapure water to the dimethyl sulfoxide is (0.03-0.05):1, and the mass ratio of potassium hydroxide to the Kevlar fiber is 3:(1.5-2.5);

[0009] S2, preparation of PVA-co-PE nanofibers;

[0010] S3, prepare Kevlar nanofiber hydrogel, take a certain amount of PVA-co-PE nanofiber prepared in step S2 and a mixed solution of a certain amount of water and isopropanol, add them to the Kevlar nanofiber hydrogel, break them with a beater, stir them evenly, then add a cross-linking agent, cross-link them under stirring conditions to obtain a Kevlar / PVA-co-PE composite solution, and then filter and hot press to obtain a Kevlar nanofiber composite membrane; the cross-linking agent is obtained by mixing concentrated hydrochloric acid, glutaraldehyde, and ultrapure water, and 0.01-0.03mL of concentrated hydrochloric acid, 1-4mL of glutaraldehyde, and 5-15mL of ultrapure water are added to every 100mL of Kevlar / PVA-co-PE composite solution.

[0011] As a further improvement of the present invention, in the Kevlar nanofiber composite membrane prepared in step S3, the mass ratio of PVA-co-PE nanofiber to Kevlar nanofiber is (0.1-0.5):1.

[0012] As a further improvement of the present invention, in step S3, 100 mL of a mixed solution of water and isopropanol is added to every 0.025 g-0.05 g of Kevlar nanofiber hydrogel, wherein the volume ratio of water to isopropanol is (45-55): (45-55).

[0013] As a further improvement of the present invention, in step S3, the preparation method of the Kevlar nanofiber hydrogel is to take a certain amount of Kevlar nanofiber dispersion, add 20 times the volume of ultrapure water and stir.

[0014] As a further improvement of the present invention, in step S3, the cross-linking time is 1-3 hours and the cross-linking temperature is 25-30°C.

[0015] As a further improvement of the present invention, in step S3, the filter membrane used is a nylon filter membrane, a polypropylene filter membrane or a polyethersulfone filter membrane with a pore size of 0.1-0.5 μm.

[0016] As a further improvement of the present invention, in step S2, the preparation method of the PVA-co-PE nanofiber is to mix cellulose acetate butyrate and PVA-co-PE masterbatch in a mass ratio of (70-90): (10-30), and then extrude through a twin-screw to obtain PVA-co-PE / CAB composite fibers, and then extract the prepared PVA-co-PE / CAB composite fibers with acetone using a Soxhlet extraction method to obtain PVA-co-PE nanofibers.

[0017] To achieve the above object, the present invention further provides a Kevlar nanofiber composite membrane, which is prepared by the preparation method described in any of the above technical solutions.

[0018] As a further improvement of the present invention, the Kevlar nanofiber composite membrane has a densely stacked layered mosaic structure.

[0019] As a further improvement of the present invention, the thickness of the Kevlar nanofiber composite membrane is between 0.041-0.069 mm, and the maximum tensile stress is between 59-82 MPa.

[0020] The beneficial effects of the present invention are:

[0021] The present invention provides a method for preparing a Kevlar nanofiber composite membrane, wherein a specific amount of PVA-co-PE nanofibers and Kevlar nanofibers are cross-linked to prepare a Kevlar nanofiber composite membrane having a densely stacked layered mosaic structure. The composite membrane provided by the present invention has excellent comprehensive performance, and its mechanical strength and durability are greatly improved compared with ordinary Kevlar nanofiber membranes. The preparation method provided by the present invention is simple to operate, economical and efficient, has high reproducibility, and is easy to expand from laboratory scale to industrial production.

[0022] (1) The Kevlar nanofiber composite membrane prepared by the preparation method provided by the present invention is crack-free, highly dense, and the cross section presents an obvious densely stacked layered mosaic structure. The layered structure, on the one hand, helps to evenly distribute the load, reduce local stress concentration, and improve the mechanical strength of the membrane. On the other hand, it can give the membrane material good processability, so that it is convenient for subsequent processing operations such as cutting, coating and lamination in practical applications, and can meet a variety of industrial and engineering application requirements; in addition, the Kevlar nanofiber and the PVA-co-PE fiber are interlocked and complementary, and a special mosaic structure is formed between the layered structures, which further improves the mechanical strength and durability of the composite membrane, so that the composite membrane can effectively resist external stress and mechanical damage, so as to enhance the overall stability of the composite membrane.

[0023] (2) The present invention uses a mixture of concentrated hydrochloric acid, glutaraldehyde, and ultrapure water in a specific ratio and amount as a crosslinking agent to fully crosslink PVA-co-PE and Kevlar nanofibers, which not only improves the interfacial bonding force of the Kevlar nanofiber composite membrane, but also makes the preparation process highly repeatable. This is because, during the crosslinking process, firstly, concentrated hydrochloric acid promotes the crosslinking reaction by protonating the hydroxyl group and providing an acidic environment, while enhancing the formation of hydrogen bonds; secondly, glutaraldehyde reacts with the functional groups (such as hydroxyl-OH, amide group-CONH-) in PVA-co-PE and Kevlar fibers to form a stable crosslinking network between the two fibers. This synergistic effect allows PVA-co-PE and Kevlar nanofibers to be fully cross-linked, forming hydrogen bonds between the amide groups (-CONH-) in the Kevlar fiber molecules and the hydroxyl groups (-OH) in the PVA-co-PE. The hydrogen bonding force works synergistically with the π-π stacking effect of the two fibers, the intermolecular induced dipole effect, the hydroxyl network effect, and the entanglement and interlocking of the molecular chains, significantly enhancing the interfacial bonding force between the two, giving the composite material excellent mechanical strength and stability.

[0024] (3) The Kevlar nanofiber composite membrane provided by the present invention has improved mechanical properties while retaining its original softness and lightness. In addition, due to the fast film-forming speed, the preparation time required in production is short and the energy consumption is low. At the same time, the composite membrane not only has the advantages of Kevlar fiber such as high strength and high modulus, high temperature resistance, chemical corrosion resistance, and light weight, but also has the characteristics of PVA-co-PE nanofiber such as high hydrophilicity, non-toxicity, good biocompatibility, good film-forming property, and low pollution. It has good application prospects in the fields of composite materials, packaging materials, and filter materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1These are scanning electron microscope (SEM) images of the nanofiber membranes prepared in Comparative Example 1 and Example 1, wherein a1 and a2 are 2000 and 10000 times SEM images of the cross section of the Kevlar nanofiber membrane (ANF), respectively, and b1 and b2 are 2000 and 10000 times SEM images of the cross section of the Kevlar nanofiber composite membrane (ANF+25% NF), respectively.

[0026] Figure 2 Figure 2 is an optical image of the nanofiber dispersion prepared in Example 1, wherein Figure c is an optical image of the Kevlar nanofiber hydrogel, and Figure d is an optical image of the Kevlar / PVA-co-PE composite solution after cross-linking of ANF and PVA-co-PE.

[0027] Figure 3 These are the optical images of the nanofiber membranes prepared in Comparative Example 1 and Example 1, wherein e1 and e2 are the optical images before and after ANF hot pressing after filtration and membrane formation, respectively, and f1 and f2 are the optical images before and after ANF+25% NF hot pressing after filtration and membrane formation, respectively.

[0028] Figure 4 1 and 2. The stress-strain curves of the nanofiber membranes prepared in Comparative Example 1, Example 1 and Example 6. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0030] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0031] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0032] The present invention provides a method for preparing a Kevlar nanofiber composite membrane. The composite membrane is prepared by cross-linking Kevlar nanofibers with PVA-co-PE nanofibers. The method significantly improves the mechanical strength and comprehensive performance of the membrane material, ensures that the composite membranes have a strong interface bonding force, and ensures the effective transmission of stress. The preparation method comprises the following steps:

[0033] S1, cutting the Kevlar fiber into small pieces, putting them into a potassium hydroxide aqueous solution, immersing them for a certain period of time, pouring a certain amount of dimethyl sulfoxide into them, and mechanically stirring them for a certain period of time to obtain a Kevlar nanofiber dispersion with a mass volume fraction of 0.1%-0.5%;

[0034] Specifically, the Kevlar fiber is cut into small segments of 4-6 mm, the immersion time is 15-25 s, the mechanical stirring time is 2-3 h, the potassium hydroxide aqueous solution is prepared with ultrapure water, the volume ratio of ultrapure water to dimethyl sulfoxide is (0.03-0.05):1, and the mass ratio of potassium hydroxide to Kevlar fiber is 3:(1.5-2.5).

[0035] Immersing the cut Kevlar fibers in a potassium hydroxide aqueous solution can provide an alkaline environment for dimethyl sulfoxide to dissolve the Kevlar fibers, thereby greatly shortening the preparation time of the Kevlar nanofiber dispersion.

[0036] S2, preparation of PVA-co-PE nanofibers;

[0037] Specifically, the preparation method of PVA-co-PE nanofibers is to mix cellulose acetate butyrate (CAB) and PVA-co-PE masterbatch in a mass ratio of (70-90): (10-30), extrude through a twin-screw extruder to obtain PVA-co-PE / CAB composite fibers, and then extract the prepared PVA-co-PE / CAB composite fibers with acetone using a Soxhlet extraction method to obtain PVA-co-PE nanofibers.

[0038] S3, prepare Kevlar nanofiber hydrogel, take a certain amount of PVA-co-PE nanofiber prepared in step S2 and a mixed solution of a certain amount of water and isopropanol, add them to the Kevlar nanofiber hydrogel, break them with a beater, stir them evenly, then add a cross-linking agent, cross-link them under stirring conditions to obtain a Kevlar / PVA-co-PE composite solution, and then filter and hot press to obtain a Kevlar nanofiber composite membrane; the cross-linking agent is obtained by mixing concentrated hydrochloric acid, glutaraldehyde, and ultrapure water, and 0.01-0.03mL of concentrated hydrochloric acid, 1-4mL of glutaraldehyde, and 5-15mL of ultrapure water are added to every 100mL of Kevlar / PVA-co-PE composite solution.

[0039] Specifically, the preparation method of Kevlar nanofiber hydrogel is to take a certain amount of Kevlar nanofiber dispersion, add 20 times the volume of ultrapure water and stir.

[0040] Specifically, the mass ratio of PVA-co-PE nanofibers to Kevlar nanofibers in the Kevlar nanofiber composite membrane is (0.1-0.5):1.

[0041] Specifically, 100 mL of a mixed solution of water and isopropanol is added to every 0.025 g to 0.05 g of Kevlar nanofiber, wherein the volume ratio of water to isopropanol is (45-55):(45-55), preferably 50:50.

[0042] Specifically, the cross-linking time is 1-3 hours and the temperature is 25-30°C.

[0043] Specifically, the filter membrane used is a nylon filter membrane, a polypropylene filter membrane or a polyethersulfone filter membrane with a pore size of 0.1-0.5 μm. Preferably, the filter membrane diameter is 50 mm.

[0044] The present invention also proposes a Kevlar nanofiber composite membrane, which is prepared according to the preparation method described in any of the aforementioned technical schemes. The composite membrane has a densely stacked layered mosaic structure, the thickness of the composite membrane is between 0.041-0.069 mm, and the maximum tensile stress is between 59-82 MPa.

[0045] The composite membrane prepared by cross-linking Kevlar nanofibers with PVA-co-PE nanofibers can significantly improve the mechanical strength and comprehensive performance of the membrane material, while retaining the original softness and lightness of the Kevlar nanofiber membrane by controlling the thickness of the membrane.

[0046] The preparation method of the Kevlar nanofiber composite membrane provided by the present invention is described below with reference to specific embodiments.

[0047] Example 1

[0048] This embodiment provides a method for preparing a Kevlar nanofiber composite membrane (ANF+25% NF), wherein the solid content of PVA-co-PE is 25%, which means that the mass ratio of PVA-co-PE nanofiber to Kevlar nanofiber is 0.25:1. The specific steps of preparation are:

[0049] S1, take 0.25g Kevlar fiber, cut it into small pieces of about 5mm, and put it into a potassium hydroxide aqueous solution with a mass volume fraction of 0.75%, wherein the mass ratio of potassium hydroxide to Kevlar fiber is 3:2, after immersion for 20s, pour in 100mL dimethyl sulfoxide, and mechanically stir for 2.5h to obtain a Kevlar nanofiber dispersion with a mass volume fraction of 0.25%;

[0050] S2, after mixing 800g CAB and 200g PVA-co-PE, the mixture is extruded by a twin-screw extruder to obtain PVA-co-PE / CAB composite fibers, and then the prepared PVA-co-PE / CAB composite fibers are extracted with acetone using a Soxhlet extraction method to obtain PVA-co-PE nanofibers.

[0051] S3, take 15mL of the Kevlar nanofiber dispersion prepared in step S1, add 20 times the volume of ultrapure water, stir and filter, and obtain a Kevlar nanofiber hydrogel. Then, weigh 0.0094g of the PVA-co-PE nanofiber prepared in step S2 and add it to the aforementioned Kevlar nanofiber hydrogel, add 100mL of a mixed solution of water and isopropanol (V 水 :V 异丙醇 =1:1). Then, the mixture was broken up with a beater to evenly disperse the two fibers, and then a cross-linking agent prepared by 0.02 mL of concentrated hydrochloric acid, 2 mL of glutaraldehyde, and 10 mL of ultrapure water was added under stirring conditions for cross-linking at 28°C for 2 h to obtain a Kevlar / PVA-co-PE composite solution. The Kevlar / PVA-co-PE composite solution was filtered using a nylon filter membrane (diameter 50 mm, pore size 0.22 μm), and finally hot-pressed to obtain ANF+25% NF.

[0052] Examples 2-6 and Comparative Example 1

[0053] The main difference between Examples 2-6 and Comparative Example 1 and Example 1 is that the PVA-co-PE nanofiber PVA-co-PE solid content is 10%, 20%, 30%, 40%, 50%, and 0%, respectively. The other contents are roughly the same as those in Example 1 and will not be repeated here. The detailed parameters are shown in Table 1.

[0054] Table 1. Differences in experimental parameters between Examples 2-6, Comparative Example 1 and Example 1

[0055]

[0056] Comparative Example 2

[0057] The main difference between Comparative Example 2 and Example 1 is that no cross-linking agent is added in step S3. The other contents are substantially the same as those in Example 1 and will not be described again. The comparative example prepares a Kevlar nanofiber composite membrane ANF+25% NF-1.

[0058] Comparative Example 3

[0059] The main difference between Comparative Example 3 and Example 1 is that in step S3, the crosslinking agent is changed to 0.005 mL concentrated hydrochloric acid, 0.5 mL glutaraldehyde, and 3 mL ultrapure water. The other contents are roughly the same as Example 1 and will not be repeated here. This comparative example prepares ANF+25% NF-2.

[0060] See also Figure 1As shown, a1 and a2 are 2000 and 10000 times SEM images of the cross section of the Kevlar nanofiber membrane prepared in Comparative Example 1, respectively. It can be seen that compared with the ordinary Kevlar nanofiber membrane, the Kevlar nanofiber composite membrane prepared by the present invention presents a densely stacked layered structure with obvious layers. On the one hand, this layered structure helps to evenly distribute the load, reduce local stress concentration, and improve the mechanical strength of the membrane. On the other hand, it can give the membrane material good processability, so that it is convenient for subsequent processing operations such as cutting, coating and lamination in practical applications, which can meet a variety of industrial and engineering application requirements; in addition, in the composite membrane, the Kevlar nanofiber and the PVA-co-PE fiber are interlocked and complementary, and a special interlocking structure is formed between the layered structures, which further improves the mechanical strength and durability of the composite membrane, so that the composite membrane can effectively resist external stress and mechanical damage, and enhance the overall stability of the composite membrane.

[0061] See also Figure 2 As shown, c is an optical image of the Kevlar nanofiber hydrogel in Example 1, and d is an optical image of the Kevlar / PVA-co-PE composite solution after cross-linking of ANF and PVA-co-PE in Example 1. It can be seen that the Kevlar nanofiber hydrogel is relatively transparent and slightly blue, while the Kevlar / PVA-co-PE composite dispersion is white, indicating that a cross-linking reaction has occurred between Kevlar and PVA-co-PE. The Kevlar / PVA-co-PE composite solutions prepared in Examples 1-6 and Comparative Examples 2-3 were placed in an environment of about 26°C, and the placement time was recorded when precipitation began to occur, as shown in Table 2.

[0062] Table 2. Stable storage time of Kevlar / PVA-co-PE composite solution

[0063] project Placement time (min) Example 1 45 Example 2 25 Example 3 42 Example 4 38 Example 5 31 Example 6 22 Comparative Example 2 3 Comparative Example 3 8

[0064] Please refer to the table above. The Kevlar / PVA-co-PE composite solutions prepared in Examples 1-6 can be placed stably for a period of time. Among them, the composite solution prepared in Example 1 can be placed for 45 minutes, showing good stability, while the Kevlar / PVA-co-PE composite solutions prepared in Comparative Examples 2-3 can only be placed for 3 minutes and 8 minutes, respectively, indicating that an appropriate amount of cross-linking agent can fully cross-link the Kevlar fiber and the PVA-co-PE fiber, and the dispersion is most stable when the PVA-co-PE solid content is 25%. The Kevlar / PVA-co-PE composite solution has good stability to avoid precipitation during the suction filtration membrane forming process, which leads to the problem of uneven thickness of the composite membrane. This good stability can not only improve the quality and performance of the composite membrane, but also prolong the operation time, so that the experiment has high reproducibility, which is of great significance for the preparation of high-quality composite membrane materials.

[0065] See also Figure 3 As shown, e1 and e2 are the optical images of ANF before and after hot pressing after filtration, respectively, and f1 and f2 are the optical images of ANF+25% NF before and after hot pressing after filtration. It can be seen that compared with before and after ANF hot pressing, the ANF+25% NF membrane material presents a uniform light white color, indicating that the PVA-co-PE nanofibers are evenly distributed on the surface and inside of the composite membrane; the surface of ANF+25% NF after hot pressing is smooth and flat, and the color is uniform, indicating that the prepared composite membrane is compact and has uniform thickness.

[0066] The thickness and maximum tensile stress of the membranes prepared in Examples 1-6 and Comparative Examples 1-3 were tested. The thickness was measured by using a dispersion of the same concentration to prepare three identical membranes, and the thickness was tested at three different positions on each membrane, and the average value was calculated. The maximum tensile stress was measured by using a dispersion of the same concentration to prepare three identical membranes, and three 5×20 mm rectangular samples were cut from each membrane, and the maximum tensile stress was tested one by one and the average value was calculated. The thickness and maximum tensile stress of the Kevlar nanofiber membrane are shown in Table 3.

[0067] The durability of the Kevlar nanofiber membranes prepared in Examples 1-6 and Comparative Examples 1-3 was tested. The specific steps were as follows: the membrane material was cut into rectangular samples of 5×20 mm, the membrane material was manually folded in half along the specified crease direction with a folding angle of 180 degrees, and the tensile properties were tested after repeated folding 500 times. The maximum tensile stress obtained by the test is also shown in Table 3.

[0068] Table 3. Thickness, maximum tensile stress and durability of Kevlar nanofiber membranes prepared by different processes

[0069]

[0070] See also Figure 4As shown, the stress-strain curves of the Kevlar nanofiber membranes prepared in Example 1, Example 6 and Comparative Example 1 are shown. Combined with Table 3, it can be seen that compared with ANF, after adding PVA-co-PE, the maximum tensile stress of the Kevlar fiber composite membrane increases significantly, and with the increase of the solid content of PVA-co-PE, the maximum tensile stress shows a trend of first increasing and then decreasing. This is because Kevlar fiber is mainly composed of aromatic polyamide, which has extremely strong intermolecular hydrogen bonds and π-π stacking effects, while PVA-co-PE is a polyethylene-acetal copolymer, which contains a large number of hydroxyl (-OH) groups in its molecules. During the cross-linking process, hydrogen bonds are formed between the amide groups (-CONH-) in the Kevlar fiber molecules and the hydroxyl groups (-OH) in the PVA-co-PE. The hydrogen bonding force works synergistically with the π-π stacking effect of the two fibers, the intermolecular induced dipole effect, the hydroxyl network effect, and the entanglement and interlocking of the molecular chains, significantly enhancing the interfacial bonding force between the two, giving the composite material excellent mechanical strength and stability. When the solid content of the PVA-co-PE fiber is 25%, the intermolecular synergistic effect is optimal.

[0071] Please continue to refer to Table 3, and you can see that the thickness of the Kevlar nanofiber prepared in Examples 1-6 is 0.041-0.069 mm, among which ANF+25% NF with the best mechanical properties is only 0.007 mm thicker than the ordinary Kevlar nanofiber membrane, which means that the composite membrane provided by the present invention has improved the mechanical properties while retaining the original softness and lightness of the ordinary Kevlar nanofiber membrane, and because the film forming speed is fast, the preparation time required in production is short and the energy consumption is low.

[0072] Please continue to refer to Table 3, it can be seen that after folding 500 times, the maximum tensile stress of ANF+25% NF is still 76MPa, which is only reduced by 6MPa, while the maximum tensile stress of ANF membrane without adding PVA-co-PE fiber is reduced by 13MPa. It shows that the Kevlar nanofiber composite membrane prepared by the present invention has good durability, and the influence of bending on its mechanical properties is small.

[0073] Please continue to refer to Table 3. It can be seen that the Kevlar nanofiber composite membrane obtained without adding a cross-linking agent or by changing the amount and ratio of the cross-linking agent has poor mechanical properties and poor durability, which indicates that adding an appropriate amount of a cross-linking agent with a specific ratio helps to fully cross-link PVA-co-PE with the Kevlar nanofiber, improve the interfacial bonding strength of the Kevlar nanofiber composite membrane, and thus improve its mechanical properties and durability.

[0074] In summary, the present invention combines PVA-co-PE nanofibers with low pollution, non-toxicity, good biocompatibility and excellent film-forming properties with Kevlar nanofibers to prepare Kevlar nanofiber composite membranes. This method enables the composite membranes to have strong interfacial bonding forces through cross-linking, ensuring the effective transmission of stress. The composite membrane prepared by this method presents a densely stacked layered mosaic structure, which significantly improves the mechanical strength and durability of the membrane material. When PVA-co-PE nanofibers account for 25% of the mass of Kevlar nanofibers, the prepared Kevlar nanofiber composite membrane has the best mechanical strength and durability.

[0075] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a Kevlar nanofiber composite membrane, characterized in that: The steps include: S1, cutting the Kevlar fiber into small pieces, putting it into a potassium hydroxide aqueous solution, immersing it for 15-25 seconds, pouring a certain amount of dimethyl sulfoxide, and mechanically stirring it for 2-3 hours to obtain a Kevlar nanofiber dispersion with a mass volume fraction of 0.1%-0.5%; wherein the potassium hydroxide aqueous solution is prepared with ultrapure water, the volume ratio of the ultrapure water to the dimethyl sulfoxide is (0.03-0.05):1, and the mass ratio of potassium hydroxide to the Kevlar fiber is 3:(1.5-2.5); S2, preparation of PVA-co-PE nanofibers; S3, prepare Kevlar nanofiber hydrogel, take a certain amount of PVA-co-PE nanofiber prepared in step S2 and a mixed solution of a certain amount of water and isopropanol, add them to the Kevlar nanofiber hydrogel, break them with a beater, stir them evenly, then add a cross-linking agent, cross-link them under stirring conditions to obtain a Kevlar / PVA-co-PE composite solution, and then filter and hot press to obtain a Kevlar nanofiber composite membrane; the cross-linking agent is obtained by mixing concentrated hydrochloric acid, glutaraldehyde, and ultrapure water, and 0.01-0.03mL of concentrated hydrochloric acid, 1-4mL of glutaraldehyde, and 5-15mL of ultrapure water are added to every 100mL of Kevlar / PVA-co-PE composite solution.

2. The method for preparing the Kevlar nanofiber composite membrane according to claim 1, characterized in that: In the Kevlar nanofiber composite membrane prepared in step S3, the mass ratio of PVA-co-PE nanofiber to Kevlar nanofiber is (0.1-0.5):

1.

3. The method for preparing the Kevlar nanofiber composite membrane according to claim 2, characterized in that: In step S3, 100 mL of a mixed solution of water and isopropanol is added to every 0.025 g to 0.05 g of Kevlar nanofiber hydrogel, wherein the volume ratio of water to isopropanol is (45-55): (45-55).

4. The method for preparing the Kevlar nanofiber composite membrane according to claim 3, characterized in that: In step S3, the preparation method of the Kevlar nanofiber hydrogel is to take a certain amount of Kevlar nanofiber dispersion, add 20 times the volume of ultrapure water and stir.

5. The method for preparing the Kevlar nanofiber composite membrane according to claim 4, characterized in that: In step S3, the cross-linking time is 1-3 hours and the cross-linking temperature is 25-30°C.

6. The method for preparing the Kevlar nanofiber composite membrane according to claim 5, characterized in that: In step S3, the filter membrane used is a nylon filter membrane, a polypropylene filter membrane or a polyethersulfone filter membrane with a pore size of 0.1-0.5 μm.

7. The method for preparing the Kevlar nanofiber composite membrane according to claim 1, characterized in that: In step S2, the preparation method of the PVA-co-PE nanofiber is as follows: cellulose acetate butyrate and PVA-co-PE masterbatch are mixed in a mass ratio of (70-90): (10-30), and then PVA-co-PE / CAB composite fibers are obtained by twin-screw extrusion. Then, the prepared PVA-co-PE / CAB composite fibers are extracted with acetone using a Soxhlet extraction method to obtain PVA-co-PE nanofibers.

8. A Kevlar nanofiber composite membrane, characterized in that: The Kevlar nanofiber composite membrane is prepared according to the preparation method described in any one of claims 1-7.

9. The Kevlar nanofiber composite membrane according to claim 8, characterized in that: The Kevlar nanofiber composite membrane has a densely stacked layered mosaic structure.

10. The Kevlar nanofiber composite membrane according to claim 9, characterized in that: The thickness of the Kevlar nanofiber composite membrane is between 0.041-0.069 mm, and the maximum tensile stress is between 59-82 MPa.

Citation Information

Patent Citations

  • A method for preparing a high-strength thermally conductive film based on Kevlar nanofibers

    CN110004712B

  • Titanium dioxide flexible composite film with Kevlar fiber as substrate and preparation method of titanium dioxide flexible composite film

    CN116407960A

Cited By

  • Preparation method of aramid nanofiber composite nanofiltration membrane

    CN120900437A